Weak-form efficiency of shariah-compliant finance stocks: Evidence from KLSE of Malaysia - Qaiser Munir; Sook, Ching Kok (2022)
We examine the weak-form efficient market hypothesis (EMH) for the selected Shariah-compliant finance stocks from the Kuala Lumpur Stock Exchange (KLSE) from 1/17/92 to 8/26/2022. Based on the ADF and artificial neural network (ANN) unit root tests, our results suggest that all three Shariah-compliant stocks are efficient before the COVID-19 period. Our results of ANN test suggest that BURSA and BIMB are inefficient during the COVID-19 period. These results have some notable policy implications.